Controlled Directional Motions of Molecular Vehicles, Rotors, and Motors: From Metallic to Silicon Surfaces, a Strategy to Operate at Higher Temperatures. Issue 12 (2nd December 2015) - Chérioux, Frédéric; Galangau, Olivier; Palmino, Frank; Rapenne, Gwénaël
Abstract: In the last decade, many nanomachines with controlled molecular motions have been studied, mainly on metallic surfaces, which are easy to obtain very clean, and are stable over months. However, the studies of mechanical properties of nanomachines are mainly performed at very low temperatures, usually between 5 and 80 K, which prevents any kind of applications. In this Minireview, we will present our strategy to operate at higher temperatures, in particular through the use of semiconducting silicon surfaces. We also review our best achievements in the field through some examples of rotating molecular machines that have been designed, synthesized, and studied in our groups. On metallic surfaces, the nanovehicles are molecules with two or four triptycenes as wheels and the molecular motor is built around a ruthenium organometallic center with a piano‐stool geometry and peripheric ferrocenyl groups. On semiconducting silicon surfaces, vehicles are also made from triptycene fragments and the rotor is a pentaphenylbenzene molecule. Abstract : Turning up the heat : This Minireview describes the deposition and study of molecular vehicles and motors on noble metals with scanning tunneling microscopy at very low temperature and our strategy to operate at higher temperatures by using semiconducting silicon surfaces.